Taxonomic status of the amphi-Atlantic species Plesionika acanthonotus (Caridea: Pandalidae): a multi-locus and morphological approach - Cardoso, Irene A.; Rodríguez-Rey, Ghennie T.; Terossi, Mariana; Bartilotti, Cátia; Serejo, Cristiana S. (Zootaxa, 2019)
Deep-sea shrimps of the species Plesionika acanthonotus (Smith, 1882) and P. holthuisi Crosnier & Forest, 1968 are morphologically similar and exhibit overlapping amphi-Atlantic distributions. In the literature, through morphological studies, there are reports of doubts about the validity of P. holthuisi and some authors believe that the eastern and western Atlantic populations of P. acanthonothus could represent two distinct species. The objective of the present study was to use molecular data to elucidate the taxonomic status of the two populations of P. acanthonothus. DNA sequences of two mitochondrial genes (16S rDNA and Cytochrome Oxidase subunit I) and a nuclear gene (Histone 3) were obtained for both species and for both populations of P. acanthonotus. The sequences were also obtained from Genbank for comparison. The trees (separate and multi-locus/partitioned genes) were generated by Bayesian Inference analyzes, and genetic divergence (Kimura-2-parameters) was also calculated. All specimens that had their DNA sequenced were examined morphologically to confirm their identification; morphological variations were noted. The genetic data showed that Plesionika holthuisi is closely related to P. acanthonotus, but clearly separated, indicating that P. holthuisi is a valid species. In the multi-locus analysis, the P. acanthonothus specimens were divided into two clades, one with the eastern Atlantic specimens and another with the western Atlantic specimens. However, this genetic separation was considered to be a population structuring for three reasons: (1) the genetic divergences of the two mitochondrial genes between these two groups (eastern Atlantic X western Atlantic) were smaller than the interspecific divergence for Plesionika; (2) the P. acanthonothus sequences of the Histone 3 gene showed no genetic variation; (3) in the analyzed individuals, no valid morphological character was found to support this separation. Thus, the conclusion of this study is that P. holthuisi probably is a valid species and P. acanthonothus presents two populations with mitochondrial divergences that could be in the process of speciation, but which currently represent only one species.